"Adding salt to wounds": Parentification among children living with parents with mental illness during the COVID-19 pandemic and the role of social workers. (March 2021) - Cudjoe, Ebenezer; Kwabia, Debora Daisy; Chiu, Marcus Yu Lung; Abdullah, Alhassan
Children living with a parent with mental illness experience challenges as some may take on the roles of their parents. Physical distancing restrictions introduced because of the COVID-19 pandemic means that many children will spend more time at home which could heighten the impact of parental mental illness. For many of these children, engaging in activities with peers provides them a sort of normal life outside their family environment. However, face-to-face interactions with others outside the family may be limited under existing public health protocols. Moreover, services for children in families where there is parental mental illness may also be limited considering limitations placed on people's movements to reduce the rate of COVID-19 infections. This opinion article draws on existing research and practitioner knowledge to suggest how social workers can continue supporting these children and their families during the COVID-19 pandemic. Support, in the form of online interventions, have been recommended to meet the needs of children during the pandemic period. Online support is timely because it is easily accessible and often does not require face-to-face interactions. Social workers and other human service professionals should be able to adapt existing online services to the needs of the children which they serve.